Improving english language learners' public speaking performance using online peer feedback - Satanihpy @ Saidalvi, Aminabibi (2016)
The ubiquitous use of peer feedback in a public speaking course is lending a new level of credence as an educational tool. However, little is known about its efficacy in an online environment. To address this gap, the present study investigated the usage of online peer feedback within an Online Public Speaking Course (OPSC) website which was developed to allow students to interact within the context of giving and receiving feedback and practicing their own public speaking. Using a qualitative phenomenological research design, the study investigated i) types of online peer feedback, ii) students’ experience of using these feedbacks, and iii) changes in the students’ public speaking performance. Students were required to present public speaking, upload on the OPSC website for peers’ feedback and revised their speech. Evaluation of the students’ speech performance, online peer feedback record, students’ journal entries and semistructured focus group interview were the source of data collection. Results of the study showed firstly, students use three types of online peer feedback; Corrective, Motivational and Graphical feedback. Secondly, online peer feedback provided students the experience of i) better confidence level, ii) independent learning, iii) discussion among peers, and iv) infinite revision opportunities. Thirdly, online peer feedback improved students’ engagement with the audience with better i) delivery and voice control skills, ii) language and proficiency skills, and iii) organized presentation skills. It is recommended that all public speaking instructors, teachers and trainers experience online peer feedback in public speaking course as the study has provided innovative ways in the methodology of public speaking skills.